(3GdGLQGe GdHjhdhLj hGdCef GdHTQj(B:s (3hGbY GdMeGjI hSHd GdehGLgI GdbGfhfjI (B/s - (3GdLed(B, (3MGRe MSfs ((3CHhXHj (B- (3OhdI GdGeGQGJ GdYQHjI GdeJMOI(B:s (3eQcR GdGeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI(B,s, 2022)
(3JYJeO GdLQjeI GdHjhdhLjI Ydi GdJbGfI GdMjhjI, Ch GdLjfjI, aj JZjjQ GdNhGU GdHjhdhLjI ddCMjGA ef LQGKje, hajQhSGJ, hejcQhHGJ, hZjQgG; hRjGOI NWhQJgG, Ke fT`QgG, Ch GSJZdGdgG YOGFkqjG; dEMOGK BKGQ cGQKjI HHfj GdHT`Q hHjFI GdCMjGA hGdeMjW GdMjhj; hef Knqe JgOO GdGYJOGAGJ GdHjhdhLjI Cef GdHT`QjI hHbGAgG, hJHpqOO ebpqheGJgG GdJfehjI(B. (3hJMGhd GdSjGSI GdJT`QjYjI (B-(3Ydi GdUYjnOjf GdOhdj hGdhWfj(B- (3eLGHgI XGgQI GdELQGe GdHjhdhLj; hJJYOO eLGdGJ GdMeGjI hSHdgG; SYkjG Edi VHW GdCfTWI GdHjhdhLjI, hGYJQGV NWhGJ ESGAI GSJNOGe JbGfJgG, haQV GdQbGHI hGdET`QGa GdeSJenqQjf ef GdLgGJ GdQSejI aj GdOhdI(B. (3hbO HrQgfJ GdCMOGK Ydi YLR cKjQ ef GdCfXeI GdbGfhfjI Yf eLGHgI GdgLeGJ GdHjhdhLjI, Ch GdMO ef GfYcGSGJgG GdSdHjI Ydi GdCef GdHT`Qj(B. (3hHQZe cKQI GdJMPjQGJ GdOhdjI, hGdbhGYO GdbGfhfjI, hGdeYGgOGJ hGdUchc hGdGJaGbjGJ GdOhdjI, GdJj JMXQ gPg GdGYJOGAGJ; jShO GdnqJnNoqha ef EecGfjI GeJOGO GdYOhGf GdHjhdhLj fMh EMOGK aXGFY EfSGfjI cHQi; fXkQG Edi JYoqPQ JMOjO GeJOGOg GdLZQGaj, Ch GdJMoqce ajg(B. (3hef gfG JJVM CgejI gPg GdOQGSI aj eYGdLI XGgQI GdELQGe GdHjhdhLj ef efXhQ bGfhfj Ohdj hhWfj; EP JJYnqbH fTCI gPG GdELQGe, heXGgQ NWhQJg hYOGFg, hGfYcGSGJg GdSdHjI Ydi GdCef GdHT`Qj, hYdi MQcI GdJfejI; hJfGbT hGbY GdMeGjI GdbGfhfjI GdbGFeI, hEWGQgG, hhSGFdgG, hGdefgL GdSdje ddMeGjI GdaGYdI(B. (3hJSJYQV GdOQGSI CaVd GdeeGQSGJ GdYGdejI hCMOKgG aj eLGd GdMeGjI GdbGfhfjI VO GdELQGe GdHjhdhLj, hLghO GdeTpqQY GdEeGQGJj dehGLgJg; hef Knqe JYQV ebJQMGJ dJWhjQ GdEWGQ GdbGfhfj decGaMI gPG GdNWQ GdLSje(B.s
Keywords: (3GdCSdMI GdHjhdhLjI (B((3bGfhf Ohdj(B)s; (3CSdMI GdOeGQ GdTGed (B((3bGfhf Ohdj(B)s; (3GdCSdMI (B-- (3bhGfjf h JTQjYGJs; (3GdCSdMI GdHjhdhLjI (B-- (3bhGfjf h JTQjYGJ (B-- (3GdEeGQGJ GdYQHjI GdeJMOIs